#TITLE_ALTERNATIVE# - Hary Tjahja Soedibya (NIM 311 94 010), Petrus
Abstract : Food as sources of nutrients and energy are highly determinating materials for organisms to achieve their fitness. The availability of food sources in the environment varies, both quantitatively and qualitatively. This diversity, either those of plant or animal origin is due to environmental changes. It is because of the high diversity, many organisms face frequently any choice of food to consume, which is actually not their main food. To cope with this sort of change, optimal efforts of physiological adaptation to maintain or to achieve maximal fitness are required. Based on the problem, a study on the efforts of physiological adaptation using aquatic animal of gouramy (Osphronemus gouramy Lac.) was carried out. The fish was chosen because there is still a controversy whether it is herbivorous, carnivorous or omnivorous. The concept used to solve the problem was the alocation of energy budget. The concept of energy budget is basically the balance between food or energy sources as intake and absorbed energy to proceed metabolism, growth or that excreted in faeces and urine. Based on the concept, the difference in alocation of energy budget is principally a strategy to self defense against environmental changes. Despite the existing controversy about gouramy, feeding it as a herbivorous fish gives rise to fitness. This mean that gouramy conducts the process of physiological adaptation. It is the capability, which determines whether an organism could optimize the alocation of energy budget from its body or not. The success of optimizing the alocation of energy budget was performed in this study in terms of increase in body weight and activity. The latter was measured with distance travelled, resting, ambulatory and stereotype time. This study was aimed to compare many phenotypic variations probably to occur due to feeding variations. To do this, gouramies were fed on Tubifex powder, fish powder, Alocasia macrorhiza (L) Scott leaf powder (control), Eic;iornia crassipes (Mart.) Solms leaf powder, and mixture of fish and Alocasia leaf powder. This study was done in laboratory scale, and all parameters afecting the value of energy budget were analyzed. They were food digestibility, absorption, efficiency, oxygen consumption and fish behaviour. The statistical method employed was analysis of variance followed by Kruskal-Wallis test. The results revealed that there was high significant difference in the alocation of energy budget between gouramy fed on food of plant origin and those fed on food of animal origin, which was indicated by the absorbed energy for metabolism and growth, as well as by the excreted energy via faeces and urine. Gouramy fed on Tubifex alocated the energy from food for metabolism 64.69 %, for growth 20.46 %, and to excrete via faeces and urine 14.72 % and 0.13 % respectively. On the other hand, gouramy consuming Alocasia leaf powder, alocated the absorbed energy for metabolism 58.44 %, for growth 7.52 %, and to excrete via faeces and urine 33.93 % and 0,11 % respectively. From the phenomenon, it could be stated that alocation of energy is an effort to adapt physiologically against food availability. The control of energy budget is one of gouramys strategies to maintain their maximal fitness represented by the value of growth rate. Energy losses via faeces and urine in the gouramy fed on food of plant origin was higher than those consuming food of animal origin. This high level of energy loss decreased directly the energy alocation required for metabolism and also for growth. The growth rate of gouramy fed on Tubifex seemed to be higher (0.84 %/days) than those consuming Alocasia leaf powder (0,43 %o/days). The high growth rate of gouramy fed on food of animal origin was because of the high values of physiological parameters such as food digestibility, absorption, efficiency, oxygen consumption and fish behaviour. Oppositely, the low growth rate of gouramy fed on food of plant origin was due to the high energy loss through faeces. This was caused by the difficulty of food digestion (5,63). This difficulty led to the requirement of mechanical action of muscle in food digestion, causing high energy demand (63). The high energy demand was represented by the high oxygen consumption measured, 0.76 mg/g/h. This high oxygen consumption was caused by the digestion of carbohydrate to simple glucose (8). Another parameter supporting the results was the low distance travelled and directly followed by a long resting time. This activity was related to the fish strategy in controlling energy alocation. It could be concluded from the results that gouramy controlled the alocation of energy budget optimally to achieve their needs maximally. This physiological adaptation is a biological concept indicating that an organism has the capability to alter the alocation of energy budget to overcome environmental changes. From the evaluation on the values of alocation of energy budget, it can be stated that this variation of energy budget was caused by the capability of gouramy to conduct optimally the physiological processes, especially in utilizing the food consumed. This was supported by the analysis on the values of physiological parameters affecting food digestion and absorption. The value of protein digestibility shown by gouramy consuming Tubifex was the highest, 96.11 %.